2016
DOI: 10.1136/jech-2015-206744
|View full text |Cite
|
Sign up to set email alerts
|

Are adolescent orphans more likely to be HIV-positive? A pooled data analyses across 19 countries in sub-Saharan Africa

Abstract: Background Despite extensive resources and numerous programs directed towards orphans in sub-Saharan Africa, evidence of their disadvantage is surprisingly limited. While initial research suggests that orphans are at greater risk of being HIV-positive, the evidence suffers from important methodological and geographic limitations. Methods To rigorously test disparities in HIV prevalence related to orphanhood and parental HIV status in sub-Saharan Africa, we used Demographic and Health Survey data from 19 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…12 School attendance has proved a significant tool in the fight against HIV/AIDS. 15 Moreover, AIDS orphans and non-HIV-related orphans tend to be more vulnerable to sexual victimization when they lack the opportunity of education, 5…”
Section: Economic Sanctions Child Health and Hivmentioning
confidence: 99%
See 2 more Smart Citations
“…12 School attendance has proved a significant tool in the fight against HIV/AIDS. 15 Moreover, AIDS orphans and non-HIV-related orphans tend to be more vulnerable to sexual victimization when they lack the opportunity of education, 5…”
Section: Economic Sanctions Child Health and Hivmentioning
confidence: 99%
“…For instance, 13.4 million children were living without one or both parents in 2016 because of AIDS . And as Kidman and Anglewicz find, orphans who lose their mother or both parents are two to three times more likely to become HIV infected. While sanction literature finds negative effects of sanctioning on health and marginalized populations, little research has examined the effects on child HIV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have identified adolescent orphans as a high-risk group for HIV; several have found that orphans are two to three times more likely to have acquired HIV by the time they reach adolescence than non-orphaned peers. 6,7 Humanitarian groups, governments, and donors have specifically targeted orphans in HIV prevention initiatives. 8,9 …”
mentioning
confidence: 99%
“…So far, studies of HIV risk factors or risk factors for the uptake of interventions against HIV have generally been limited to specific sub-populations, [3][4][5][6][7] sub-national regions, 3,[5][6][7][8][9] or countries. [10][11][12][13][14][15][16][17] Recent studies included up to 31 SSA countries, but narrowly focused their inquiries to examine, for example, the association between socio-economic inequalities, 18 high-risk sexual behavior, 19 smoking, 20 or HIV-related stigma 21 with HIV testing, treatment uptake, ART adherence, or HIV prevalence.…”
Section: Introductionmentioning
confidence: 99%